Development of Immuno-Enzymatic Monoclonal Tests-Systems for the Detection of Glanders and Melioidosis Agents - A. A. Kytmanov; G. D. Elagin; G. V. Kuklina; D. V. Pechenkin; O. O. Fomenkov; A. V. Eremkin; S. S. Ipatov; E. R. Ziganshin (Проблемы особо опасных инфекций, 2018)
Objective of the study was the development of immune-enzymatic monoclonal test-kit for detecting glanders and melioidosis agents. Materials and methods. We used microbial cultures and hybrid cell lines obtained from the collection of the «48th Central Research Institute» of the Ministry of Defense of the Russian Federation. Hybridoma cells were incubated in the peritoneal cavity of BALB/c mice. Preparations of glanders and melioidosis monoclonal antibodies were isolated from the ascetic fluids through precipitation with ammonium sulfate and purification by means of ion-exchange chromatography. Specific components of the test-kits were subjected to freeze drying in corresponding protective media. Study of diagnostic properties of the developed test systems was performed using ELISA. Results and conclusions. We have obtained preparations of monoclonal antibodies in vivo, as well as isolated and purified immunoglobulins from ascetic fluids. We also selected the pairs of monoclonal antibodies for manufacturing specific components. Experimental series of immune-enzymatic monoclonal test-systems allowing for specific detection of glanders and melioidosis causative agents in concentrations ranging from 0.5·106 CFU/ml and higher were made. The absence of cross-reactivity with closely related saprophytes and heterologous microorganisms in concentrations of 1,0·108 CFU/ml was shown. Demonstrated was the possibility in principle to differentiate between Burkholderia malleiand Burkholderia pseudomallei using ELISA. Test systems are promising for follow up state registration as medical products for in vitro diagnostics.